Biogel‐Derived Polycrystalline MnO Spheres/S‐Doped Carbon Composites with Enhanced Performance as Anode Materials for Lithium‐Ion Batteries. Issue 6 (27th March 2017) - Yang, Hongzhan; Liu, Wei; Zhang, Yuan; Wang, Huanlei; Liu, Shuang; Chen, Shougang; Cheng, Fengli; Zhao, Shuping; Hao, Enchao
Abstract: To meet the practical requirement of advanced storage equipment, electrode materials with low cost, high performance, and readily available large‐scale production are of intensive concern. In this work, a natural marine biomass, gelidium amansii, was used to fabricate novel polycrystalline MnO spheres/S‐doped carbon composites (MnO/SC) with hierarchical porosity by using a simple bio‐sol‐gel and pyrolysis process. By inducing biogels, the unique composites of polycrystalline MnO spheres encapsulated and interwoven in a sulfur‐doped carbon net were created, which leads to a higher loading of active materials in contrast to other reported bio‐derived MnO/C materials. As anode materials for lithium‐ion batteries, the obtained MnO/SC composites delivered a high reversible capacity of 1100 mAh g −1 after 200 cycles at 0.2 A g −1 and a superior long‐term cycling performance of over 500 mAh g −1 after 1000 cycles even at the high current density of 2 A g −1 . Therefore, the present work represents a feasible large‐scale fabrication approach toward high‐performance electrode materials on the basis of rich natural biogels. Abstract : Fabrication through nature : A novel polycrystalline MnO sphere/S‐doped carbon composite with hierarchical porosity is constructed by using a cost‐effective synthetic approach with natural marine biomass, gelidium amansii, as renewable precursors. The composite shows potential as an outstanding anode material for lithium‐ion batteries.